2008
DOI: 10.1007/s11239-008-0194-1
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and methylenetetrahydrofolate reductase C677T and A1298C polymorphisms in Tunisian patients with severe coronary artery disease

Abstract: Elevation in homocysteine and methylenetetrahydrofolate reductase (MTHFR) gene variants, C677T and A1298C, have been linked with atherothrombosis. However their exact contribution to coronary artery disease (CAD) remains controversial. Moreover, data from Tunisian patients are scarse. We examined the association of MTHFR C677T and A1298C, and changes in plasma homocysteine in 352 Tunisian patients with angiographically-demonstrated CAD, and 390 age and gender-matched healthy subjects. Significantly higher freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
3
16
1
Order By: Relevance
“…However, the T-A haplotype conferred an increased risk for coronary atherosclerosis severity, with a frequency of 40% in the high Gensini score group compared with 34.6% in the low Gensini score group. These results are in agreement with the finding by L. Ghazouani et al [27] where the C-A haplotype also indicated a protective role against CAD with an OR = 0.39 and 95% CI = 0.29-0.52. The T-A haplotype provided an increased risk for CAD with an OR = 2.35 and 95% CI = 1.62-3.38, which is also consistent with our findings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the T-A haplotype conferred an increased risk for coronary atherosclerosis severity, with a frequency of 40% in the high Gensini score group compared with 34.6% in the low Gensini score group. These results are in agreement with the finding by L. Ghazouani et al [27] where the C-A haplotype also indicated a protective role against CAD with an OR = 0.39 and 95% CI = 0.29-0.52. The T-A haplotype provided an increased risk for CAD with an OR = 2.35 and 95% CI = 1.62-3.38, which is also consistent with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…The T-A haplotype provided an increased risk for CAD with an OR = 2.35 and 95% CI = 1.62-3.38, which is also consistent with our findings. In our study, however, the C-C and T-C haplotype frequency showed no difference between the two groups, whereas the Ghazouani et al [27] study indicated that they conferred an increased risk for CAD. Differences in ethnicity, dietary intake, exposure to environmental risk factors and sample size may be responsible for the discrepancies in the results.…”
Section: Discussioncontrasting
confidence: 88%
“…24 Increased levels of inflammatory markers, such as the high-sensitivity C-reactive protein (hs-CRP), are predictive for increased risk of cardiovascular diseases and associated with atherosclerotic disease and insulin resistance. 25,26 Our study indicates that patients with MS-associated T2DM, the serum hs-CRP level and HOMA-IR are higher in those patients with MTHFR TT genotype than those with CC and CT genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,8 A number of studies have explored the use of folic acid and vitamin B12 to decrease these levels, 9,10 but this relationship may not be as straightforward as once hoped. The recent ‘Vitamins to Prevent Stroke’ (VITATOPS) trial 11 examined the long-term daily effects of folic acid, vitamin B6, and vitamin B12 in reducing tHcy through conversion and excretion; 12 the regimen proved safe, but not significantly more effective than placebo in reducing major vascular events.…”
Section: Introductionmentioning
confidence: 99%